Synthesis of Cu/Co-hybrid MOF as a multifunctional porous compound in catalytic applications, synthesis of new nanofibers, and antimicrobial and cytotoxicity agents - Asiri, Mohammed; Jawad BahrAluloom, Yamamah; Abdullateef Alzubaidi, Mazin; Mourad Mohammed, Ibrahim; Suliman, Muath; Ramzy Muhammad, Eman; Abed, Ahmed S.; Abodi Ali, Fattma; Hadrawi, Salema K.; Alsalamy, Ali H.; Alwave, Marim (Frontiers in Materials, 2023)
Several biological properties of metal-organic frameworks and fiber compounds have been reported. Therefore, the combination of these two structures can have unique properties. In this study, by the ultrasonic technique, copper-containing MOFs nanostructures and cobaltcontaining MOFs nanostructures were synthesized. Then novel Cu/Co-Hybrid MOF nanostructures using the ultrasonic method were synthesized. Synthesized Cu/Co-Hybrid MOF nanostructures were used as a new and efficient recyclable catalyst in the synthesis of pyrano[2,3-c]pyrazoles derivatives using the 4-component reaction of phenylhydrazine, ethyl acetoacetate, malononitrile, and aldehyde. In the following, by electrospinning and using Cu/Co-Hybrid MOF nanostructures and polyvinyl alcohol, novel Cu/Co-Hybrid MOF/PVA fibers nanostructures were synthesized. The structure of Cu/Co-Hybrid MOF nanostructures and Cu/Co-Hybrid MOF/PVA fibers nanostructures using BET, TGA, FTIR, SEM, and XRD were identified and confirmed. In biological studies, the anti-bacterial, anti-fungal, and cytotoxicity activity of Cu/Co-Hybrid MOF and Cu/Co-Hybrid MOF/PVA fibers nanostructures were evaluated. In investigating the catalytic activity of Cu/Co-Hybrid MOF, pyrano[2,3-c]pyrazole derivatives were synthesized with higher efficiency and less time than previously reported methods. High anti-bacterial (against gramnegative and gram-positive strains) and anti-fungal properties of synthesized Cu/Co-Hybrid MOF nanostructures and Cu/Co-Hybrid MOF/PVA fibers nanostructures were observed (MIC between 16-256 μg/mL), which were higher than some commercial drugs. In the investigation of cytotoxicity activity, the effectiveness on breast cancer cells was studied, and maximum cell proliferation and viability for Cu/Co-Hybrid MOF and Cu/Co-Hybrid MOF/PVA fibers nanostructures, 38% and 38% than control in a concentration of 200 μg/ml in 48 hours, respectively, were observed. The high catalyst and biological properties of the synthesized nanoparticles can be attributed to the presence of nano-sized bioactive metals, and their high specific surface area. The significant physical-chemical properties obtained for synthesized nanoparticles in this study can be related to the desirable synthesis methods, the development of materials with high purity, and the incorporation of nanostructures in hybrid nature.